sece
(d) 1-sina
(d)
Prove the following:
tano
(a)
= 1
cose coto
cosece cote
(b)
=
sino tane
sec0 - 1
(c)
sinée
sec?0
1
1
+
= 2sec a
1
1 + sina
1 + sine cose
(e)
+
2seco
1 + sino
cose
1
1
f) 1 + cose
+
1 - coso
= 2 cosec²0
1
g) sece – tane
= seco + tano
1
= coseco + coto
coseco - cote
sind + cose
seco + coseco
sino.cose
tano + tana
)
cote + cota
tana . tano
h)
i)
Ivedanta​

Respuesta :

Answer:

Step-by-step explanation:

sinée

sec?0

1

1

+

= 2sec a

1

1 + sina

1 + sine cose

(e)

cote + cota

tana . tano

h)

i)

Ivedanta​

Otras preguntas